Monolithic catalyst for purifying tail gas in high-activity formaldehyde production as well as preparation method and application of monolithic catalyst
By introducing nitrogen-doped support and indium elements into the catalyst, combined with equal volume impregnation method and gradient drying technology, the high cost and poor dispersion of precious metal integral catalysts in formaldehyde exhaust purification is solved, and efficient removal of carbon monoxide and dimethyl is achieved. ether reduces production costs and improves catalyst activity and stability.
Patent Information
- Application Number
- CN202411296797.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The existing precious metal monolithic catalysts have problems such as high cost, poor dispersion of precious metals, and unstable coatings in the purification of formaldehyde exhaust gas, and it is difficult to efficiently remove carbon monoxide and dimethyl ether, affecting the activity and life of the catalyst.
The integrated catalyst supported by nitrogen-doped support and indium elements and precious metals are used to load during the impregnation stage. Through equal volume impregnation method and gradient drying technology, the precious metals are evenly distributed in the support pores, reducing the precious metal content and improving the catalyst activity.
The exhaust gas purification of high-active formaldehyde production is achieved, which reduces the catalyst cost, improves the dispersion of precious metals and catalyst stability, significantly improves the removal efficiency of carbon monoxide and dimethyl ether, and extends the catalyst life.
Smart Images

Figure BDA0005046276120000121 
Figure BDA0005046276120000122
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a high-activity formaldehyde production tail gas purification integral catalyst and a preparation method and application thereof. Background Art
[0002] 1,4-Butanediol (BDO) is an important organic chemical and fine chemical raw material. It is the basic raw material for the production of polybutylene terephthalate (PBT) engineering plastics and PBT fibers. PBT plastics are one of the five most promising engineering plastics. Formaldehyde is an important raw material for the production of BDO. The iron-molybdenum methanol air oxidation method to produce formaldehyde is a common industrial formaldehyde preparation method. The formaldehyde tail gas mainly contains unabsorbed formaldehyde, unreacted methanol and by-products dimethyl ether and carbon monoxide. Among these tail gas components, carbon monoxide is the most difficult to purify due to its high concentration, and carbon monoxide is highly toxic. It will combine with hemoglobin in human blood to make it lose its oxygen-carrying capacity, thereby causing people to suffocate and die from lack of oxygen. Therefore, carbon monoxide cannot be directly discharged into the atmosphere. Dimethyl ether is also a toxic gas that can damage the human respiratory system, skin and nervous system. Therefore, it is necessary to find a method that can efficiently purify carbon monoxide and dimethyl ether in formaldehyde tail gas.
[0003] Among the many methods for purifying carbon monoxide and dimethyl ether, catalytic oxidation is widely used due to its advantages such as low cost, low energy consumption and easy operation. The reaction is an exothermic reaction, and the heat released by the reaction can maintain the reaction. The key to the catalytic oxidation method is the catalyst. The formaldehyde tail gas has a large air velocity and high water content, so a low-gas resistance and high-stability monolithic catalyst should be used. At the same time, precious metals are widely used in the field of catalytic oxidation due to their excellent catalytic activity. Precious metal monolithic catalysts currently have problems such as high cost, poor precious metal dispersion, and unstable coating.
[0004] Invention patent CN112156777B discloses a method for preparing a honeycomb monolithic precious metal catalyst. The slurry in the preparation method is prepared by directly adding cerium-zirconium-aluminum composite oxide and water-soluble precious metal compounds into deionized water, and then milling the slurry by a planetary ball mill. Although the method is simple, the precious metal component and the cerium-zirconium-aluminum composite oxide cannot be mixed evenly, and the precious metal component is mostly on the surface of the carrier rather than in the pores, which makes the precious metal dispersion poor. The present invention adopts an equal volume impregnation method and gradient drying to allow the active components to be evenly distributed in the pores of the carrier.
[0005] Invention patent CN115970687A discloses a Pt-based natural gas exhaust purification catalyst, which has two inner and outer coatings. The inner coating includes metal Pt, Pd, and cerium-zirconium composite oxide, and the outer coating includes a Pt layer and a Rh layer. The multi-coated catalyst is not only cumbersome to prepare, but also has a high consumption of precious metals. The multi-coating is also easy to fall off, the catalyst cost is high and the stability is poor. The precious metals and non-precious metals of the present invention are loaded onto the catalyst during the impregnation stage, which reduces the steps of catalyst preparation and the consumption of precious metals is also lower.
[0006] At present, precious metal integral catalysts are rarely involved in formaldehyde tail gas purification, and the catalyst cost is relatively high. In order to reduce the cost, it is necessary to reduce the content of precious metals in the catalyst and improve the dispersion of precious metals, but at the same time, the activity and life of the catalyst will be reduced. To solve these problems, the present invention introduces indium elements and nitrogen doping on the basis of precious metal catalysts. The introduced indium can form a MO bond or a MO-In bond with the precious metal M, so that the precious metal is in an oxidized state to stabilize the precious metal element. The nitrogen atom can replace lattice oxygen, increase the amount of active oxygen, and enhance the activity of the catalyst. The lone pair of electrons of the nitrogen atom can also change the electronic properties of the carrier, and can anchor the precious metal element. The content of the precious metal is reduced while ensuring that the activity of the catalyst remains unchanged, so as to reduce the catalyst cost. Summary of the invention
[0007] One of the purposes of the present invention is to provide a high-activity formaldehyde production tail gas purification integral catalyst to solve the problems of high carbon monoxide content in the tail gas of partial oxidation of methanol to formaldehyde and high catalyst cost in the prior art.
[0008] The second object of the present invention is to provide a method for preparing the high-activity formaldehyde production tail gas purification integral catalyst.
[0009] The third object of the present invention is to provide the application of the high-activity formaldehyde production tail gas purification integral catalyst.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] The invention discloses a high-activity formaldehyde production tail gas purification monolithic catalyst, which uses cordierite honeycomb ceramic as a matrix to load the catalyst; the catalyst includes an active component, an auxiliary agent, and a nitrogen-doped carrier that loads the active component and the auxiliary agent;
[0012] The active component is Pt or / and Pd, and its content is 0.05-0.7wt.% of the mass of the nitrogen-doped carrier;
[0013] The auxiliary agent includes In2O3, the content of which is 2-7wt% of the mass of the nitrogen-doped carrier;
[0014] The nitrogen-doped carrier includes oxygen storage materials and Al2O3; the oxygen storage materials include CeO2, ZrO2, La2O3 and Y2O3; the mass of the nitrogen-doped carrier is 100%, containing CeO2: 2-10wt%, ZrO2: 0-5wt%, La2O3: 0-7wt%, Y2O3: 0-10wt%, and Al2O3: 75-90wt%.
[0015] In some embodiments of the present invention, the content of the active component is 0.05 to 0.5 wt. % of the mass of the nitrogen-doped carrier.
[0016] In some embodiments of the present invention, the method for preparing the nitrogen-doped carrier comprises the following steps:
[0017] Step 1. Add water to the aluminum salt and the salt of the oxygen storage material to prepare a salt solution, and add water to dissolve the hydrothermal nitrogen source to prepare an alkali solution, then mix the salt solution and the alkali solution, react by microwave-assisted hydrothermal method, and then centrifuge, wash and dry the reaction precipitate to obtain a nitrogen-containing carrier;
[0018] Preferably, the salt of the oxygen storage material comprises a nitrogen-containing cerium salt;
[0019] Further preferably, the salt of the oxygen storage material also includes at least one of nitrogen-containing zirconium salts, lanthanum salts, and yttrium salts;
[0020] Step 2. Preparation of nitrogen-doped carrier: Disperse the nitrogen-containing carrier prepared in step 1 and the pyrolyzed nitrogen source in water, perform ultrasonication, centrifugation, precipitation washing, drying, calcination and pyrolysis to obtain the nitrogen-doped carrier.
[0021] In some embodiments of the present invention, in step 1, the nitrogen-containing cerium salt is ammonium cerium nitrate, the nitrogen-containing zirconium salt is ammonium zirconium carbonate, the lanthanum salt, yttrium salt, and aluminum salt are corresponding nitrates; and the hydrothermal nitrogen source is at least one of glycine, dopamine, urea, glutamic acid, melamine, and ammonium bicarbonate;
[0022] Preferably, in step 1, the molar ratio of total metal cations in the salt solution to the hydrothermal nitrogen source is 2:1 to 1:5;
[0023] Preferably, in step 1, the microwave-assisted hydrothermal reaction comprises the following steps: mixing the salt solution and the alkali solution and pouring them into a pressurized hydrothermal reactor, introducing a protective gas to control the pressure to 3-5 MPa, and reacting at 150-200° C. in a microwave parallel reactor for 8-24 hours;
[0024] Preferably, in step 1, the precipitate is washed by centrifugation until the pH value of the supernatant is 7.
[0025] In some embodiments of the present invention, in step 2, the pyrolysis nitrogen source is one of polydopamine, pyrrole, pyridine, and polyacrylamide;
[0026] Preferably, the mass ratio of the nitrogen-containing carrier to the pyrolytic nitrogen source is 5:1 to 15:1;
[0027] Preferably, the ultrasonication is carried out under heating conditions; more preferably, the ultrasonication is carried out at 40 to 60°C;
[0028] Preferably, the ultrasound time is 2 to 4 hours;
[0029] Preferably, in step 2, the calcination and pyrolysis temperature is 500-900° C., the calcination time is 2-4 hours, and the calcination is carried out under a nitrogen atmosphere.
[0030] The method for preparing a high-activity formaldehyde production tail gas purification monolithic catalyst disclosed in the present invention comprises the following steps:
[0031] Step A. Preparing a noble metal salt and an indium salt into an aqueous solution, adding a nitrogen-doped carrier, loading the noble metal and indium on the carrier by an impregnation method, and then drying and calcining to obtain a catalyst powder;
[0032] Step B: Mix a binder, an acid, an additive and a catalyst powder to prepare a slurry, apply the slurry on one side of a cordierite honeycomb ceramic, and obtain a monolithic catalyst after drying and calcining.
[0033] In some embodiments of the present invention, in step A, the noble metal salt is one of nitrate and chloride, and the indium salt is one of indium nitrate and indium sulfate;
[0034] Preferably, in step A, the active component and the auxiliary agent are loaded on the carrier by an equal volume impregnation method;
[0035] Preferably, in step A, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours.
[0036] In some embodiments of the present invention, in step B, the binder includes at least one of alumina sol, silica sol, pseudo-boehmite, and boehmite;
[0037] The acid includes at least one of oxalic acid, acetic acid, citric acid, and hydrochloric acid;
[0038] The additive comprises at least one of starch, polyvinyl pyrrolidone, hydroxypropyl methylcellulose and hydroxymethyl cellulose;
[0039] Preferably, the solid content of the slurry is 30 to 50 wt%;
[0040] Preferably, the slurry is coated on one side of the cordierite honeycomb ceramic and blown evenly with high-pressure air, and the loading amount of the slurry is 70 to 150 g / L;
[0041] Preferably, in step B, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours.
[0042] The invention discloses the application of the above-mentioned high-activity formaldehyde production tail gas purification integral catalyst in the purification of methanol-to-formaldehyde tail gas.
[0043] In some embodiments of the present invention, the carbon monoxide concentration in the methanol-to-formaldehyde tail gas is 0.1-2v%, the dimethyl ether concentration is 0.1-0.5v%, the oxygen concentration is 3-7v%, the methanol concentration is 0.1-0.2v%, the water vapor concentration is 3-5v%, and the volume space velocity is 2000-30000h -1 , the reaction temperature is 150-250°C, and the bed pressure is normal pressure.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The present invention adopts nitrogen element to dope the carrier and introduces indium element. Nitrogen can replace part of oxygen, change the coordination number, enhance the binding ability between the noble metal and the carrier, anchor the noble metal, and indium element can form MO bond or MO-In bond with the noble metal M, so that the noble metal is in an oxidized state to stabilize the noble metal element. In addition, nitrogen element and indium element can also improve the electronic properties of the material through electron transfer regulation, thereby improving the catalytic activity of the material. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Example 1
[0048] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0049] (1) Weigh 4.75 g of ammonium cerium nitrate, 2.58 g of ammonium zirconium carbonate, 1.56 g of lanthanum nitrate, 0.30 g of yttrium nitrate and 70.42 g of aluminum nitrate, place them in the same container, add water to dissolve, and adjust the volume to 200 mL to obtain a salt solution; weigh 79.55 g of glycine, add water to dissolve and adjust the volume to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution and pour them into a hydrothermal reactor, fill with nitrogen and pressurize to 3 MPa, react at 200° C. in a microwave parallel reactor for 16 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0050] (2) 20 g of the nitrogen-containing carrier and 3 g of melamine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and placed in a tube furnace, and calcined at 900° C. for 3 h in a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0051] (3) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.03 g of Pt, 0.07 g of Pd and 0.83 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0052] (4) 2 g of pseudo-boehmite and 2 g of acetic acid were ball-milled into a gel, and 0.2 g of starch and 20 g of
[0053] The catalyst powder is ball-milled and mixed to form a slurry with a solid content of 40wt%; the slurry is coated on one side of the cordierite honeycomb ceramic and blown evenly with high-pressure air. The loading amount of the slurry is 100g / L, and the temperature is 60℃, 90℃,
[0054] After step drying at 120°C and calcination at 550°C for 2h, the monolithic catalyst S1 was obtained.
[0055] Example 2
[0056] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0057] (1) Weigh 3.42 g of ammonium cerium nitrate, 3.16 g of ammonium zirconium carbonate, 1.84 g of lanthanum nitrate and 71.42 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 64.33 g of urea, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 180° C. in a microwave parallel reactor for 18 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0058] (2) 20 g of the nitrogen-containing carrier and 2 g of dopamine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace and calcined at 700° C. for 3 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0059] (3) Pt(NO3)2, Pd(NO3)2 and ammonium indium nitrate were prepared into a 10 mL precursor solution containing 0.02 g of Pt, 0.08 g of Pd and 0.56 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0060] (4) 2 g of aluminum sol and 2 g of citric acid are ball-milled into a gel. After the gel is formed, 0.2 g of hydroxymethyl cellulose is added and mixed with 20 g of catalyst powder by ball-milling to prepare a slurry with a solid content of 40 wt%. The slurry is coated on one side of a cordierite honeycomb ceramic and evenly blown with high-pressure air. The slurry has a loading amount of 100 g / L. The slurry is step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst S2.
[0061] Example 3
[0062] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0063] (1) Weighing 4.63 g of ammonium cerium nitrate, 1.73 g of ammonium zirconium carbonate, 2.36 g of yttrium nitrate and 71.34 g of aluminum nitrate, placing them in the same container, adding water to dissolve them, and fixing the volume to 200 mL to obtain a salt solution; weighing 84.76 g of ammonium bicarbonate, dissolving them in water and fixing the volume to 200 mL to obtain an alkaline solution; mixing the salt solution and the alkaline solution, pouring them into a hydrothermal reaction kettle, reacting them at 160° C. in a microwave parallel reactor for 18 h, centrifuging the precipitate, washing it until the supernatant is neutral, and drying it to obtain a nitrogen-containing carrier;
[0064] (2) 20 g of the nitrogen-containing carrier and 3 g of urea were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and placed in a tube furnace, and calcined at 750° C. for 5 h in a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0065] (3) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.01 g of Pt, 0.04 g of Pd and 0.63 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0066] (4) 2 g of pseudo-boehmite and 2 g of oxalic acid were ball-milled into a gel. After the gel was formed, 0.2 g of polyvinyl pyrrolidone was added and mixed with 20 g of catalyst powder by ball-milling to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst S3.
[0067] Example 4
[0068] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0069] (1) Weigh 5.94 g of ammonium cerium nitrate, 2.48 g of ammonium zirconium carbonate, 0.97 g of lanthanum nitrate, 2.65 g of yttrium nitrate and 66.20 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 150.96 g of glutamic acid, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 200° C. in a microwave parallel reactor for 24 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0070] (2) 20 g of the nitrogen-containing carrier and 2.7 g of pyridine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace for calcination at 830° C. for 4 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0071] (3) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.04 g of Pt, 0.06 g of Pd and 1.15 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0072] (4) 2 g of pseudo-boehmite and 2 g of citric acid were ball-milled into a gel. After the gel was formed, 0.2 g of hydroxypropyl methylcellulose was added and mixed with 20 g of catalyst powder by ball-milling to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst S4.
[0073] Example 5
[0074] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0075] (1) Weigh 4.06 g of ammonium cerium nitrate, 3.45 g of ammonium zirconium carbonate, 2.52 g of lanthanum nitrate, 3.49 g of yttrium nitrate and 62.81 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 79.10 g of ammonium bicarbonate, dissolve it in water and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 150° C. in a microwave parallel reactor for 18 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0076] (2) 20 g of the nitrogen-containing carrier and 2.3 g of glycine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace and calcined at 550° C. for 5 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0077] (3) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.07 g of Pt, 0.03 g of Pd and 1.40 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0078] (4) 2 g of silica sol and 2 g of acetic acid were ball-milled into gel, and 0.2 g of polyvinyl pyrrolidone was added after gelation. The mixture was mixed with 20 g of catalyst powder and ball-milled to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of cordierite honeycomb ceramics and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain the integral catalyst S5.
[0079] Example 6
[0080] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0081] (1) Weigh 3.38 g of ammonium cerium nitrate, 2.70 g of lanthanum nitrate, 2.15 g of yttrium nitrate and 69.77 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 160.79 g of dopamine, dissolve it in water and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 180° C. in a microwave parallel reactor for 22 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0082] (2) 20 g of the nitrogen-containing carrier and 2.5 g of urea were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace and calcined at 600° C. for 4 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0083] (3) Pt(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.1 g of Pt and 0.75 g of In. Pt and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, dried in steps of 60°C, 90°C, and 120°C, and calcined at 550°C for 3 h to obtain a catalyst powder;
[0084] (4) 2 g of pseudo-boehmite and 2 g of citric acid were ball-milled into gel. After gelation, 0.2 g of starch was added and mixed with 20 g of catalyst powder by ball-milling to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of cordierite honeycomb ceramics and evenly purged with high-pressure air. The slurry loading amount was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain the integral catalyst S6.
[0085] Example 7
[0086] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0087] (1) Weigh 3.89 g of ammonium cerium nitrate, 0.94 g of ammonium zirconium carbonate, 1.04 g of lanthanum nitrate, 0.79 g of yttrium nitrate and 74.90 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 82.82 g of glycine, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 200° C. in a microwave parallel reactor for 16 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0088] (2) 20 g of the nitrogen-containing carrier and 2 g of melamine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace for calcination at 630° C. for 3 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0089] (4) Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.05 g of Pd and 0.98 g of In. Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, specifically as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, dried in steps of 60°C, 90°C, and 120°C, and calcined at 550°C for 3 h to obtain a catalyst powder;
[0090] (5) 2 g of aluminum sol and 2 g of citric acid were ball-milled into gel, and 0.2 g of starch was added after gelation. The mixture was then ball-milled with 20 g of catalyst powder to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The slurry had a loading capacity of 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst S7.
[0091] Example 8
[0092] This embodiment discloses a method for preparing the catalyst of the present invention, specifically:
[0093] (1) Weigh 6.30 g of ammonium cerium nitrate, 1.20 g of lanthanum nitrate and 72.78 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 64.30 g of urea, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 180° C. in a microwave parallel reactor for 24 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0094] (2) 20 g of the nitrogen-containing carrier and 2.8 g of pyrrole were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace and calcined at 560° C. for 4 h under a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0095] (4) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.02 g of Pt, 0.05 g of Pd and 0.42 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, dried in steps of 60°C, 90°C and 120°C, and calcined at 550°C for 3 h to obtain a catalyst powder;
[0096] (5) 2 g of pseudo-boehmite and 2 g of oxalic acid were ball-milled into a gel. After the gel was formed, 0.2 g of hydroxymethyl cellulose was added and mixed with 20 g of catalyst powder by ball-milling to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst S8.
[0097] Comparative Example 1
[0098] Compared with Example 1, the carrier in this comparative example is not nitrogen-doped, specifically:
[0099] (1) Weighing 2.83 g of cerium nitrate, 2.05 g of zirconium nitrate, 1.56 g of lanthanum nitrate, 0.30 g of yttrium nitrate and 70.42 g of aluminum nitrate, placing them in the same container, adding water to dissolve them, and fixing the volume to 200 mL to obtain a salt solution; weighing 56.16 g of sodium carbonate, adding water to dissolve them and fixing the volume to 200 mL to obtain an alkaline solution; mixing the salt solution and the alkaline solution, pouring them into a hydrothermal reaction kettle, reacting them at 200° C. in a microwave parallel reactor for 16 h, centrifuging the precipitate, washing until the supernatant is neutral, and drying to obtain a carrier;
[0100] (2) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.03 g of Pt, 0.07 g of Pd and 0.83 g of In. Pt, Pd and In were loaded on the carrier by an equal volume impregnation method, specifically as follows: 20 g of the carrier prepared in step (1) was added to the precursor solution and then rapidly stirred, dried in steps of 60°C, 90°C and 120°C, and calcined at 550°C for 3 h to obtain a catalyst powder;
[0101] (3) 2 g of pseudo-boehmite and 2 g of acetic acid were ball-milled into gel, and 0.2 g of starch was added after gelation. The mixture was ball-milled with 20 g of catalyst powder to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The slurry had a loading amount of 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst D1.
[0102] Comparative Example 2
[0103] Relative to Example 1, no auxiliary agent was added in this comparative example, specifically:
[0104] (1) Weigh 4.75 g of ammonium cerium nitrate, 2.58 g of ammonium zirconium carbonate, 1.56 g of lanthanum nitrate, 0.30 g of yttrium nitrate and 70.42 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 79.55 g of glycine, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 200° C. in a microwave parallel reactor for 16 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0105] (2) 20 g of the nitrogen-containing carrier and 3 g of melamine were thoroughly mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and placed in a tube furnace, and calcined at 900° C. for 3 h in a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0106] (3) Pt(NO3)2 and Pd(NO3)2 were prepared into a 10 mL precursor solution containing 0.03 g of Pt and 0.07 g of Pd, and Pt and Pd were loaded on the nitrogen-doped carrier by an equal volume impregnation method, specifically as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C, and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0107] (4) 2 g of pseudo-boehmite and 2 g of acetic acid were ball-milled into gel, and then 0.2 g of starch and 20 g of catalyst powder were added and ball-milled to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst D2.
[0108] Comparative Example 3
[0109] Compared with Example 1, the precious metal content is increased in this comparative example, specifically:
[0110] (1) Weigh 4.75 g of ammonium cerium nitrate, 2.58 g of ammonium zirconium carbonate, 1.56 g of lanthanum nitrate, 0.30 g of yttrium nitrate and 70.42 g of aluminum nitrate, place them in the same container, add water to dissolve, and dilute to 200 mL to obtain a salt solution; weigh 79.55 g of glycine, add water to dissolve and dilute to 200 mL to obtain an alkaline solution; mix the salt solution and the alkaline solution, pour them into a hydrothermal reactor, react at 200° C. in a microwave parallel reactor for 16 h, centrifuge the precipitate, wash until the supernatant is neutral, and dry to obtain a nitrogen-containing carrier;
[0111] (2) 20 g of the nitrogen-containing carrier and 3 g of melamine were fully mixed and ground, and then the mixed material was dispersed in deionized water, ultrasonicated at 50° C. for 3 h, the dispersion was centrifuged, the precipitate was washed and dried, and then placed in a tube furnace, and calcined at 900° C. for 3 h in a nitrogen atmosphere to obtain a nitrogen-doped carrier;
[0112] (3) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.06 g of Pt, 0.14 g of Pd and 0.83 g of In. Pt, Pd and In were loaded on the nitrogen-doped carrier by an equal volume impregnation method, as follows: 20 g of the nitrogen-doped carrier was added to the precursor solution and then rapidly stirred, and then dried in steps of 60°C, 90°C and 120°C, and then calcined at 550°C for 3 h to obtain a catalyst powder;
[0113] (4) 2 g of pseudo-boehmite and 2 g of acetic acid were ball-milled into gel, and then 0.2 g of starch and 20 g of catalyst powder were added and mixed, and then a slurry with a solid content of 40 wt% was prepared. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The loading amount of the slurry was 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst D3.
[0114] Comparative Example 4
[0115] Compared with Example 1, the carrier in this comparative example is not nitrogen-doped, and the precious metal content is increased, specifically:
[0116] (1) Weighing 2.83 g of cerium nitrate, 2.05 g of zirconium nitrate, 1.56 g of lanthanum nitrate, 0.30 g of yttrium nitrate and 70.42 g of aluminum nitrate, placing them in the same container, adding water to dissolve them, and fixing the volume to 200 mL to obtain a salt solution; weighing 56.16 g of sodium carbonate, adding water to dissolve them and fixing the volume to 200 mL to obtain an alkaline solution; mixing the salt solution and the alkaline solution, pouring them into a hydrothermal reaction kettle, reacting them at 200° C. in a microwave parallel reactor for 16 h, centrifuging the precipitate, washing until the supernatant is neutral, and drying to obtain a carrier;
[0117] (2) Pt(NO3)2, Pd(NO3)2 and indium nitrate were prepared into a 10 mL precursor solution containing 0.06 g of Pt, 0.14 g of Pd and 0.83 g of In. Pt, Pd and In were loaded on the carrier by an equal volume impregnation method, specifically as follows: 20 g of the carrier prepared in step (1) was added to the precursor solution and then rapidly stirred, dried in steps of 60°C, 90°C and 120°C, and calcined at 550°C for 3 h to obtain a catalyst powder;
[0118] (3) 2 g of pseudo-boehmite and 2 g of acetic acid were ball-milled into a gel, and 0.2 g of starch was added after the gel was formed. The mixture was ball-milled with 20 g of catalyst powder to prepare a slurry with a solid content of 40 wt%. The slurry was coated on one side of a cordierite honeycomb ceramic and evenly purged with high-pressure air. The slurry had a loading capacity of 100 g / L. The slurry was step-dried at 60°C, 90°C, and 120°C, and calcined at 550°C for 2 h to obtain an integral catalyst D4.
[0119] Performance Testing:
[0120] The performance tests were conducted on Examples 1 to 8 and Comparative Examples 1 to 4 obtained by the present invention, wherein the specifications of the monolithic catalyst were 22×22×50 mm cylinders, and the raw gas was divided into low-concentration gas and formaldehyde tail gas, wherein the carbon monoxide content in the low-concentration gas was 0.1 v%, and the oxygen content was 20 v%; the carbon monoxide content in the formaldehyde tail gas was 1.47 v%, and the oxygen content was 5.3 v%, the concentration of dimethyl ether was 0.33 v%, the methanol was 0.11 v%, and the water vapor was 3.64 v%. The test air velocity was 20000 h -1 The test pressure is normal pressure. The test results are shown in Table 1 and Table 2.
[0121] Table 1 Catalyst performance for purifying CO in low concentration gas
[0122]
[0123] Table 2 Catalyst performance for purifying CO in formaldehyde tail gas
[0124]
[0125] Table T 90 Indicates the temperature at which the conversion rate reaches 90%, T 50 and T 10 Similarly, it can be seen from Table 1 and Table 2 that the catalyst of the present invention has excellent catalytic performance for CO. By comparing S1 and D1, it can be found that nitrogen doping greatly reduces the activation temperature of CO, making T 10 , T 50 and T 90 Compared with S1 and D2, the loading of non-precious metals can also improve the performance of the catalyst. Compared with S1 and D3, after the carriers were nitrogen-doped, the increase in the precious metal content had little effect on the improvement of the catalyst performance. However, compared with D1 and D4, when the carriers were not nitrogen-doped, the precious metal content increased and the catalyst performance was greatly improved. This shows that nitrogen doping can narrow the performance gap between catalysts with different precious metal contents, which can reduce the content of precious metals in the catalyst to save production costs.
[0126] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A high-activity formaldehyde production tail gas purification monolithic catalyst, characterized in that: The catalyst is loaded on a cordierite honeycomb ceramic as a matrix; the catalyst comprises an active component, an auxiliary agent, and a nitrogen-doped carrier that loads the active component and the auxiliary agent; The active component is Pt or / and Pd, and its content is 0.05-0.7wt.% of the mass of the nitrogen-doped carrier; The auxiliary agent includes In2O3, the content of which is 2-7wt% of the mass of the nitrogen-doped carrier; The nitrogen-doped carrier includes oxygen storage materials and Al2O3; the oxygen storage materials include CeO2, ZrO2, La2O3 and Y2O3; the mass of the nitrogen-doped carrier is 100%, containing CeO2: 2-10wt%, ZrO2: 0-5wt%, La2O3: 0-7wt%, Y2O3: 0-10wt%, and Al2O3: 75-90wt%.
2. A high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 1, characterized in that: The content of the active component is 0.05-0.5wt.% of the mass of the nitrogen-doped carrier.
3. A high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 2, characterized in that: The preparation method of the nitrogen-doped carrier comprises the following steps: Step 1. Add water to the aluminum salt and the salt of the oxygen storage material to prepare a salt solution, and add water to dissolve the hydrothermal nitrogen source to prepare an alkali solution, then mix the salt solution and the alkali solution, react by microwave-assisted hydrothermal method, and then centrifuge, wash and dry the reaction precipitate to obtain a nitrogen-containing carrier; Preferably, the salt of the oxygen storage material includes a nitrogen-containing cerium salt; further preferably, the salt of the oxygen storage material also includes at least one of a nitrogen-containing zirconium salt, a lanthanum salt, and a yttrium salt; Step 2. Preparation of nitrogen-doped carrier: Disperse the nitrogen-containing carrier prepared in step 1 and the pyrolyzed nitrogen source in water, perform ultrasonication, centrifugation, precipitation washing, drying, calcination and pyrolysis to obtain the nitrogen-doped carrier.
4. A high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 3, characterized in that: In step 1, the nitrogen-containing cerium salt is ammonium cerium nitrate, the nitrogen-containing zirconium salt is ammonium zirconium carbonate, the lanthanum salt, yttrium salt, and aluminum salt are corresponding nitrates; and the hydrothermal nitrogen source is at least one of glycine, dopamine, urea, glutamic acid, melamine, and ammonium bicarbonate; Preferably, in step 1, the molar ratio of total metal cations in the salt solution to the hydrothermal nitrogen source is 2:1 to 1:5; Preferably, in step 1, the microwave-assisted hydrothermal reaction comprises the following steps: mixing the salt solution and the alkali solution and pouring them into a pressurized hydrothermal reactor, introducing a protective gas to control the pressure to 3-5 MPa, and reacting at 150-200° C. in a microwave parallel reactor for 8-24 hours; Preferably, in step 1, the precipitate is washed by centrifugation until the pH value of the supernatant is 7.
5. A high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 3, characterized in that: In step 2, the pyrolysis nitrogen source is one of polydopamine, pyrrole, pyridine, and polyacrylamide; Preferably, the mass ratio of the nitrogen-containing carrier to the pyrolytic nitrogen source is 5:1 to 15:1; Preferably, the ultrasonication is carried out under heating conditions; more preferably, the ultrasonication is carried out at 40 to 60°C; Preferably, the ultrasound time is 2 to 4 hours; Preferably, in step 2, the calcination and pyrolysis temperature is 500-900° C., the calcination time is 2-4 hours, and the calcination is carried out under a nitrogen atmosphere.
6. The method for preparing a high-activity formaldehyde production tail gas purification monolithic catalyst according to any one of claims 1 to 5, characterized in that: The steps include: Step A. Preparing a noble metal salt and an indium salt into an aqueous solution, adding a nitrogen-doped carrier, loading the noble metal and indium on the carrier by an impregnation method, and then drying and calcining to obtain a catalyst powder; Step B: Mix a binder, an acid, an additive and a catalyst powder to prepare a slurry, apply the slurry on one side of a cordierite honeycomb ceramic, and obtain a monolithic catalyst after drying and calcining.
7. The method for preparing a high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 6, characterized in that: In step A, the noble metal salt is one of nitrate and chloride, and the indium salt is one of indium nitrate and indium sulfate; Preferably, in step A, the active component and the auxiliary agent are loaded on the carrier by an equal volume impregnation method; Preferably, in step A, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours.
8. The method for preparing a high-activity formaldehyde production tail gas purification monolithic catalyst according to claim 6, characterized in that: In step B, the binder includes at least one of aluminum sol, silica sol, pseudo-boehmite, and boehmite; The acid includes at least one of oxalic acid, acetic acid, citric acid, and hydrochloric acid; The additive comprises at least one of starch, polyvinyl pyrrolidone, hydroxypropyl methylcellulose and hydroxymethyl cellulose; Preferably, the solid content of the slurry is 30 to 50 wt%; Preferably, the slurry is coated on one side of the cordierite honeycomb ceramic and blown evenly with high-pressure air, and the loading amount of the slurry is 70 to 150 g / L; Preferably, in step B, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours.
9. Use of the high-activity formaldehyde production tail gas purification monolithic catalyst according to any one of claims 1 to 5 in the purification of methanol to formaldehyde tail gas.
10. The use according to claim 9, characterized in that: The carbon monoxide concentration in the tail gas of the methanol-to-formaldehyde process is 0.1-2v%, the oxygen concentration is 3-7v%, the dimethyl ether concentration is 0.1-0.5v%, the methanol concentration is 0.1-0.2v%, the water vapor concentration is 3-5v%, and the volume space velocity is 2000-30000h -1 , the reaction temperature is 150-250°C, and the bed pressure is normal pressure.
Citation Information
Cited By
Multi-layer-structure broad-spectrum catalyst for formaldehyde industrial tail gas treatment and preparation method of multi-layer-structure broad-spectrum catalyst
CN122424809A
